2020
DOI: 10.1186/s12889-020-09074-w
|View full text |Cite
|
Sign up to set email alerts
|

Presentation intervals and the impact of delay on breast cancer progression in a black African population

Abstract: Background: The help-seeking interval and primary-care interval are points of delays in breast cancer presentation. To inform future intervention targeting early diagnosis of breast cancer, we described the contribution of each interval to the delay and the impact of delay on tumor progression. Method: We conducted a multicentered survey from June 2017 to May 2018 hypothesizing that most patients visited the first healthcare provider within 60 days of tumor detection. Inferential statistics were by t-test, chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Among health workforce factors, misdiagnosis was the most common and appeared in 16 studies [ 23 , 24 , 28 , 29 , 31 , 33 – 35 , 37 – 39 , 42 46 ]. Patients reported being inappropriately reassured by health workers that their breast lump was benign without a biopsy or with an incorrect biopsy interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among health workforce factors, misdiagnosis was the most common and appeared in 16 studies [ 23 , 24 , 28 , 29 , 31 , 33 – 35 , 37 – 39 , 42 46 ]. Patients reported being inappropriately reassured by health workers that their breast lump was benign without a biopsy or with an incorrect biopsy interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…The shortage of health workers and strikes were also identified as factors delaying women’s access to breast cancer treatment [ 24 , 26 , 27 , 31 , 35 , 42 , 44 ]. Studies have reported that various hospital departments turned women away because a doctor was not available [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The primary research instituted mechanisms to minimize recall bias and ensure data reliability. Details of the design and original data collection are available elsewhere [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Yet, our previous research showed that late detection and progressing to advanced disease after an early detection contributed differently to advanced-stage diagnosis and challenges of managing BC. In that research, 10% of tumors detected inadvertently were already advanced, while 30–70% of those detected early progressed to advanced-stage before diagnosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The shortage of health workers and strikes were also identi ed as factors delaying women's access to breast cancer treatment [25,27,28,32,36,42,44]. Studies have reported that various hospital departments turned women away because a doctor was not available [32].…”
Section: Strikes and Shortage Of Caregiversmentioning
confidence: 99%